Extracting datums to reconstruct CSG models from 2D engineering sketches of polyhedral shapes. (February 2022) - Plumed, Raquel; Varley, Peter A.C.; Company, Pedro; Martin, Ralph
Abstract: Our goal is to automatically generate CAD 3D models from 2D sketches as part of a design chain where models should be procedural, containing features arranged in a model tree and linked to suitable datums . Current procedural models capture much about the design intent and are easy to edit, but must be created from scratch during the detailed design state—given conceptual sketches as used by designers in the early part of the design process, current sketch-based modeling approaches only output explicit models. Thus, we describe an approach to extract high-level information directly from 2D engineering wireframe sketches and use it to complete a CSG feature tree, which serves as a model tree for a procedural 3D CAD model. Our method extracts procedural model information directly from 2D sketches in the form of a set of features, plus a set of datums and relationships between these features. We detect and analyze features of 2D sketches in isolation, and define the CSG feature tree by the parent–child relationships between features, and combine this information to obtain a complete and consistent CSG feature tree that can be transferred to a 3D modeler, which reconstructs the model. This paper focuses on how to extract the feature datums and the extrusion operation from an input 2D sketch. Graphical abstract: Highlights: We create a complete CAD model tree from a vectorized sketch of a polyhedral shape The method extracts the cross-section and auxiliary reference system of each feature The approach works when line drawing is a connected graph or disconnected subgraphs Output serves as proof of concept to demonstrate that it can build a procedural model